Kualitas Layanan, Harga, dan Kepercayaan sebagai Penentu Loyalitas Pelanggan: Literature Review Sistematis dan Sintesis Temuan Empiris Terbaru - Rizqi Hidayatul Lael; Haidar Rafli Rasyad; Muhamad Khoirul Anam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In an increasingly competitive business world with ever-increasing customer demands for the quality of services and goods, customer satisfaction and loyalty have emerged as crucial issues in today's marketing management. Under such conditions, business entities must identify the key elements that shape satisfaction and how these contribute to building customer loyalty. This paper aims to examine the nature of study results on the determinants of satisfaction and loyalty through an evaluation of several recent empirical studies. Two key questions are addressed: which elements most strongly influence customer satisfaction, and what is the intermediary function of satisfaction in explaining the relationship between marketing variables such as service quality, cost, brand image, and trust with customer loyalty. The technique employed is a qualitative literature review through a search of articles using Google Scholar and Publish or Perish (PoP). Key terms used include customer satisfaction, customer loyalty, service quality, and trust. Of the 50 articles found in the initial phase, 15 met the inclusion standards and were thoroughly reviewed. The evaluation findings reveal three dominant patterns: service and product quality are the most stable factors driving satisfaction; cost and brand image serve as supporting factors; and trust acts as an important intermediary variable. This evaluation confirms that customer satisfaction is a key component in strengthening loyalty. Future studies are recommended to expand the scope of business sectors, use a more comprehensive structural framework, and utilize a wider variety of methodological techniques.